Age-Based Mixing and Condom Use Patterns in Opposite-Sex Adult Partnerships in Hong Kong. Issue 1 (9th January 2023) - Smith, M. Kumi; Graham, Matthew; Ong, Jason J.; Tse, Desiree; Wong, William C.W.
Abstract : An analysis of age-based contact and condom use patterns in heterosexual adults in Hong Kong was performed using data from an online, population-based survey. Abstract : Background: Age-based sexual mixing data can guide design and implementation of sexually transmitted infection (STI) control interventions. It can also inform the parameterization of mathematical models of HIV and STI transmission. Data on mixing in heterosexual adults are uncommon, particularly in East Asian regions. Methods: In June 2020, egocentric network data collected from sexually active adults in Hong Kong 18 or years participating in an online, population-based survey were used to assess age-dependent contacts and condom use patterns. Age-based mixing matrices of heterosexual partnerships were constructed separately according to sex and partnership type. Results: Data from 1090 partnerships indicated highly assortative mixing among regular partners. Casual and commercial partners had larger age discrepancies, with both men and women reporting partners of the same age or younger age group. Regarding condom use, older age groups of both sexes reported less consistent use with all partner types. Particularly inconsistent use was noted in combinations of older men with younger casual/commercial female partners. Conclusions: Our findings provide novel insights potentially useful for forming sexual health and STI control policy. First, the disassortative nature of casual and commercial partnerships in both men and women suggests that they may be a mechanism for the seeding of younger generations and therefore a target of health interventions. Second, health communications may wish to target older men in particular given their higher tendency to condomless sex with casual and commercial female partners in the youngest—and therefore most susceptible—age groups, indicating a lack of the sex symmetry that was observed in regular partnerships.